Alteration of gastric microbiota and transcriptome in a rat with gastric intestinal metaplasia induced by deoxycholic acid - Xu, Zijing; Xiao, Ling; Wang, Shuaishuai; Cheng, Yuqin; Wu, Jianping; Meng, Yufen; Bao, Kaifan; Zhang, Junfeng; Cheng, Chun (Frontiers in Microbiology, 2023)
Abstract Objective: Gastric intestinal metaplasia (GIM) was an independent risk factor of gastric cancer, and bile reflux plays a key role in development of GIM. This study aimed to explore the biological mechanism of GIM induced by bile reflux in a rat model. Methods: The rats were treated with administrating 2% sodium salicylate and free drinking of 20 mmol/L sodium deoxycholate for 12 weeks, and histopathological analysis identified the occurrence of GIM. Gastric microbiota was profiled based on 16S rDNA V3-V4 region, gastric transcriptome was sequenced, and serum bile acids (BAs) was analyzed by targeted metabolomics. Spearman correlation analysis was used to construct the network among gastric microbiota, serum BAs and gene profile. Real-time polymerase chain reaction measured the expressive levels of eight genes in gastric transcriptome. Results: The GIM rats had a decreased microbial diversity in the stomach, and several dominant bacterial genera such as Limosillactobacillus and Burkholderia-Caballeronia-Paraburkholderia were significantly increased. Gastric transcriptome showed that the genes enriched in gastric acid secretion were significantly down-regulated, while the genes enriched in fat digestion and absorption were obviously up-regulated in the GIM rats. The GIM rats had four promoted serum BAs including cholic acid (CA), deoxycholic acid (DCA), taurocholic acid (TCA) and taurodeoxycholic acid (TDCA). Correlation analysis showed that Rikenellaceae RC9 gut group was significantly positive correlated with DCA and RGD1311575 (capping protein-inhibiting regulator of actin dynamics) / Fabp1 (fatty acid-binding protein, liver), reactively. In the GIM rats, RT-PCR detection showed that the expression of Dgat1 (diacylglycerol acyltransferase 1) and Fabp1 related to fat digestion and absorption was probative up-regulated, while the gastric acid secretion related genes such as Atp4b (hydrogen/potassium ATPase β), Car2 (carbonic anhydrase 2) and Gast (gastrin) were probative down-regulated. Conclusions: DCA-induced GIM enhanced the gastric digestion and absorption function, while impaired the gastric acid secretion function. The DCA - Rikenellacae RC9 gut group - RGD1311575/Fabp1 axis might play a key role in the mechanism of bile reflux-related GIM.